Surround yourself with your betters: Recommendations for adopting Industry 4.0 technologies in SMEs - Oliver Fuglsang Grooss; Mirko Presser; Torben Tambo (Digital Business, 2022)
The purpose of this paper is to review the state-of-the-art literature on Industry 4.0 and digitalisation in small and mid-sized enterprises (SMEs). The paper aims to extrapolate and organise recommendations for how to progress in these disciplines from a substantial number of studies. This is accomplished by a systematic literature review on publications within the period 2018-2021. For this purpose, a rigorous metadata analytics process is deployed to retrieve, filter, and structure large amounts of metadata to increase inclusiveness and transparency. The findings consist of 11 focus areas that are developed by extrapolating recommendations from the reviewed literature. These focus areas are structured using the technology-organisation-environment (TOE) framework, which is divided into subcategories. From these, three specific technology-focused recommendations are developed. Furthermore, the paper identifies some concerns with the current research methods due to the overall low implementation of Industry 4.0 in SMEs. This leads to suggesting that future research should engage in pragmatic research methods with attention to how digital technologies are applied in SMEs.
Keywords: 650; Industry 4.0; Digitalization; SME; TOE; Digital technology